Exploring Identity-Based Crime Victimizations: Assessing Threats and Victim Services among a Sample of Professionals. Issue 9 (2nd September 2021) - Green, Brandn; Gies, Stephen; Bobnis, Amanda; Leeper Piquero, Nicole; Piquero, Alex R.; Velasquez, Eva
ABSTRACT: An estimated 26 million American citizens per year have been victims of an identity-based crime. This study contributes to the scholarship on identity-based crime by examining serious identity-based crime victimization and the services available to help victims. This study investigated the interaction between victimized individuals and organizations and explored unmet needs for victim services. Interviews from focus groups with fifty professionals (e.g., private investigators, fraud examiners, victim service providers, and executives of firms offering victim services and protection services) working in identity-based crime victim services were used. The current study addressed two questions: 1) How do experts in the field of identity-based crime define the victims of identity theft and fraud and 2) How can the services for victims of identity-based crime be improved or expanded? Results show that professionals have a three-victim model of identity-based crime victimization, are greatly concerned about the rise in synthetic identity crime, and that identity-based crime victimization is present in a greater percentage of the population than most national estimates.